2017
DOI: 10.4172/2329-888x.1000171
|View full text |Cite
|
Sign up to set email alerts
|

The Camel's (Camelus Dromedarius) Mammary Gland Immune System in Health and Disease

Abstract: Dromedary camel (Camelus dromedarius) can survive and produce considerable amount of milk during recurrent and prolonged hot and dry environment. Camel milk considered one of the most valuable food sources due to its nutritional value. Intramammary infection and other low hygienic measurers are the main factors that undermined the camel mammary gland welfare. Available studies elaborated in detail the role of innate factors like Peptidoglycan recognition protein and Lactoferrin in camel milk as potent antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Camels, like cattle, have four mammary glands in the inguinal region responsible for the synthesis and secretion of milk proteins ( 41 ). Because camels do not have gland cisterns for storage, milk production is a reflex secretion ( 42 ). Previous studies have demonstrated that milkability traits can be assessed using udder and teat morphological traits of camels, contributing to the selection of high-producing camels ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Camels, like cattle, have four mammary glands in the inguinal region responsible for the synthesis and secretion of milk proteins ( 41 ). Because camels do not have gland cisterns for storage, milk production is a reflex secretion ( 42 ). Previous studies have demonstrated that milkability traits can be assessed using udder and teat morphological traits of camels, contributing to the selection of high-producing camels ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple literatures stated that the teat of the camel had more than one orifice and streak canal. Schwartz and Dioli (1992) and Alluwaimi et al (2017) reported that the camel teat possesses 2-3 cisterns. Zayeed et al (1991) stated that sometimes the rear quarter might have three separate mammary glands.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of an ideal udder and teat shape is an important step towards adaption to machine milking and helps to develop milking clusters suitable for the machine milking of dromedary camels [ 4 , 5 ]. The mammary gland of the camel consists of four quarters and four teats, like cows [ 6 ]. In contrast, the teats have typically two or sometimes three teat canals, and rarely just one [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%